Characteristics of geotextile clogging in MSW landfills co-disposed with MSWI bottom ash. (August 2018) - Wu, Huanan; Wang, Qian; Ko, Jae Hac; Xu, Qiyong
Graphical abstract: Highlights: Co-disposal of BA with MSW would increase the risk of geotextile clogging in landfills. Geotextile clogging mainly include CaCO3 precipitation and biofilm formation. Biomass accumulation was the main contributor to the mass increment of geotextile. The CH4 /CO2 ratio generally increased during the clogging process. CO2 in landfill gas played an important role in the clogging process. Abstract: As a main byproduct of municipal solid waste incineration (MSWI), bottom ash (BA) has become a big challenge in operating MSWI plants. The most common method for BA treatment is co-disposal with MSW in landfills, which may cause clogging in the leachate collection system (LCS). This research investigated the characteristics of geotextile clogging in landfills with BA co-disposal. The co-disposal of BA changed the characteristics of leachate, especially increasing the concentration of Ca 2+ . During the experiment, 0.14 g CaCO3 was precipitated in the MSW geotextile, while it increased to 0.52 g CaCO3 in the BA co-disposed geotextile. Based on mass balance of calcium and thermogravimetric (TG) analysis, the formation of biofilm was the main contributor to the mass increment, accounting for about 82% and 57% mass increment in the MSW and BA co-disposed geotextile, respectively. Moreover, CO2 in landfill gas played an important role in the clogging process, including CaCO3 precipitation and biofilm formation. The results suggested that the co-disposal of BA with MSW can increase the risk of geotextile clogging in landfills.